2018
DOI: 10.1007/s12560-018-9341-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bacterial Contamination as an Indicator of Viral Contamination in a Sedimentary Aquifer in Uruguay

Abstract: In Uruguay, groundwater is frequently used for agricultural activities, as well as for human consumption in urban and rural areas. As in many countries worldwide, drinking water microbiological quality is evaluated only according to bacteriological standards and virological analyses are not mentioned in the legislation. In this work, the incidence of human viral (Rotavirus A, Norovirus GII, and human Adenovirus) and bacterial (total and thermotolerant coliform and Pseudomonas aeruginosa) contamination in groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…There was no association between the detection of culturable EC and HAdV DNA and no correlation between the concentrations of these markers. Similarly, previous studies have reported an absence of association between the detection of indicator bacteria and enteric viruses in groundwater samples in Uruguay (Gamazo et al, 2018) and a lack of correlation between their concentrations in surface water in Korea (Lee et al, 2013) andin Brazil (Dalla Vecchia et al, 2015), as well as in effluents from wastewater treatment plants in South Africa (Adefisoye et al, 2016). On the other hand, a recent study by Girardi et al (2019) found a significant and direct correlation between the concentration of EC and total coliforms in relation to the concentration of adenovirus of species F in surface water in southern Brazil, but, as in the present study, such correlation was absent in relation to HAdV-C. Miao et al (2018) found a significant and positive correlation between the concentrations of total coliforms and EV, but this bacterial indicator failed to predict contamination by several other viruses, including HAdV.…”
Section: Discussionsupporting
confidence: 58%
“…There was no association between the detection of culturable EC and HAdV DNA and no correlation between the concentrations of these markers. Similarly, previous studies have reported an absence of association between the detection of indicator bacteria and enteric viruses in groundwater samples in Uruguay (Gamazo et al, 2018) and a lack of correlation between their concentrations in surface water in Korea (Lee et al, 2013) andin Brazil (Dalla Vecchia et al, 2015), as well as in effluents from wastewater treatment plants in South Africa (Adefisoye et al, 2016). On the other hand, a recent study by Girardi et al (2019) found a significant and direct correlation between the concentration of EC and total coliforms in relation to the concentration of adenovirus of species F in surface water in southern Brazil, but, as in the present study, such correlation was absent in relation to HAdV-C. Miao et al (2018) found a significant and positive correlation between the concentrations of total coliforms and EV, but this bacterial indicator failed to predict contamination by several other viruses, including HAdV.…”
Section: Discussionsupporting
confidence: 58%
“…It also meant acute gastroenteritis viruses should not be an alternative indicator of fecal or EnVs pollution even if there is prolonged virus persistence in the environment. Some previous studies [ 32 , 33 ] have also suggested that bacteriological indicators e.g., TC concentrations do not accurately reflect human viral (HRVs, HuNoVs GII, and HAdVs) dispersal in marine waters, individual groundwater, and contamination of shellfish by sewage-derived viral pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…In Colombia, the presence of RV has been detected in drinking water for consumption [39,40]. In Uruguay, RV have been detected in groundwater and wastewater [41,42].…”
Section: Rotavirus Detected In Food and Water In Latin Americamentioning
confidence: 99%